2020
DOI: 10.1186/s12885-020-07260-y
|View full text |Cite
|
Sign up to set email alerts
|

Log odds of positive lymph nodes is prognostically equivalent to lymph node ratio in non-metastatic colon cancer

Abstract: Background: Globally, colorectal cancer (CRC) is the third and second leading cancer in men and women respectively with 600,000 deaths per year. Traditionally, clinicians have relied solely on nodal disease involvement, and measurements such as lymph node ratio (LNR; the ratio of metastatic/positive lymph nodes to total number of lymph nodes examined), when determining patient prognosis in CRC. The log odds of positive lymph nodes (LODDS) is a logistic transformation formula that uses pathologic lymph node dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 28 publications
0
36
1
Order By: Relevance
“…LODDS was also used, not N stage or the number of pathologically positive lymph nodes, in the nomogram for the risk assessment of recurrence in a previous study on MTC [ 9 ]. However, LNR is thought to be easier for intuitive understanding in clinical situations because LODDS entails additional mathematical calculations [ 28 ]. As LNR provided sufficient statistical predictive power in the analysis results, further analysis of LODSS was not addressed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…LODDS was also used, not N stage or the number of pathologically positive lymph nodes, in the nomogram for the risk assessment of recurrence in a previous study on MTC [ 9 ]. However, LNR is thought to be easier for intuitive understanding in clinical situations because LODDS entails additional mathematical calculations [ 28 ]. As LNR provided sufficient statistical predictive power in the analysis results, further analysis of LODSS was not addressed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We found that NPLN, LODDS and LNR were all independent predictive factors, and LNR was superior to NPLN and LODDS by demonstrating better performance in homogeneity, statistical model fit, discrimination, and accuracy of survival prediction. LODDS was thought to be prognostically superior or equivalent to lymph node ratio in previous lung or digestive cancer studies [ 10 13 , 17 , 23 ]. Deng et al studied the predictive performance of LODDS and LNR in patients with node-positive NSCLC and chose 10 as a cutoff value of NDLN [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although NDLN and NPLN do not contribute to N classification, several studies have confirmed that higher values of NPLN, log odds of positive lymph nodes (LODDS, calculated using the formula: LODDS¼ log NPLN þ0:50 NDLN −NPLN þ0:5 ) or lymph node ratio (LNR, calculated using the formula: LNR¼ NPLN NDLN ) were related to worse prognosis for NSCLC or several other types of malignant tumors [10][11][12][13]. However, of these node classifications, which can obtain the most precise prognosis in lung AC is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…LODDS was defined as the loge [(positive nodes + 0.5)/(negative nodes + 0.5)], namely, the log of the ratio between the number of positive lymph nodes and the number of negative lymph nodes ( 22 ). X-tile (Yale University, 3.6.1) was also performed to calculate the cutoff value for LODDS group.…”
Section: Methodsmentioning
confidence: 99%